Coenhabiting Interpersonal Inter-Identities in Recurrent Social Interaction - James, Mark M.; Loaiza, Juan Manuel (Frontiers in Psychology, 2020)
We propose a view of identity beyond the individual in what we call interpersonal interidentities (IIIs). Within this approach, IIIs comprise collections of entangled stabilities that emerge in recurrent social interaction and manifest for those who instantiate them as relatively invariant though ever-evolving patterns of being (or more accurately, becoming) together. Herein, we consider the processes responsible for the emergence of these IIIs from the perspective of an enactive cognitive science. Our proposal hinges primarily on the development of two related notions: enhabiting and coenhabiting. First, we introduce the notion of enhabiting, a set of processes at the individual level whereby structural interdependencies stabilise and thereafter undergird the habits, networks of habits, and personal identities through which we make sense of our experience. Articulating this position we lean on the notion of a tendency towards an optimal grip, though offering it a developmental framing, whereby iterative states of selective openness help realise relatively stable autonomous personal identities with their own norms of self-regulation. We then extend many of the notions found applicable here to an account of social coenhabiting, in particular, we introduce the notion of tending towards a co-optimal grip as central to the development of social habits, networks of habits, and ultimately IIIs. Such structures, we propose, also emerge as autonomous structures with their own norms of self-regulation. We wind down our account with some reflections on the implications of these structures outside of the interactions wherein they come into being and offer some thoughts about the complex animations of the individual embodied subjects that instantiate them.